1976
DOI: 10.1172/jci108257
|View full text |Cite
|
Sign up to set email alerts
|

The Raji cell radioimmune assay for detecting immune complexes in human sera.

Abstract: A B S T R A C T A sensitive and simple procedure for the detection and quantitation of soluble complement (C) -fixing immune complexes in sera of patients with various disease states has been developed by utilizing C receptors on Raji cells. These cells lack membrane-bound immunoglobulin but have receptors for IgG Fc, C3b, C3d, and possibly other C proteins. Uptake experiments showed that both aggregated human gamma globulin (AHG) and 7S IgG bound to receptors for IgG Fc; however, AHG reacted with C bound to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
189
1
4

Year Published

1977
1977
1983
1983

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 652 publications
(202 citation statements)
references
References 61 publications
8
189
1
4
Order By: Relevance
“…Raji cell radioimmunoassay (RCA) was performed by the technique of Theofilopoulos et a1 (9). In our laboratory, sera of normal donors (50 individuals tested) yield control values of 47 ?…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Raji cell radioimmunoassay (RCA) was performed by the technique of Theofilopoulos et a1 (9). In our laboratory, sera of normal donors (50 individuals tested) yield control values of 47 ?…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, sera of 92 unselected patients with PSS were examined for the presence of immune complexes by three techniques: the Raji cell radioimmunoassay (RCA) (9), the Clq binding assay (ClqBA) (lo), and pattern recognition on agarose gel electrophoresis (AGE) (1 1). Correlations with clinical and other laboratory features of PSS were sought by computer analysis of an extensive database compiled on these patients in our center as part of the American Rheumatism Association Medical Information System (ARAMIS) (12).…”
mentioning
confidence: 99%
“…A potential role of immune complexes, which have been detected in SLE sera (1)(2)(3)(4), in the development of the inflammatory process in this disease has been emphasized (5)(6)(7). In view of the important role of polymorphonuclear neutrophils (PMN) in the pathogenesis of well established immune complex diseases such as experimental serum sickness (8), it was desirable to investigate possible abnormalities of PMN function in SLE.…”
mentioning
confidence: 99%
“…The occurrence of circulating immune complexes in cancer patients has been suggested first by the demonstration of serum blocking factors possibly related to immune complexes, and secondly by the direct detection of material similar to antigenantibody complexes in some patients with various types of malignancy (18,(20)(21)(22)(23)(24)(25)(26)(27)(28)39). In human leukemia, the presence of immune complexes has been suggested by the finding of renal glomerular deposits of Ig and complement in a few cases (29).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that serum blocking factors may consist of immune complexes (16)(17)(18)(19). Furthermore, several studies have indicated that antigen-antibody complexes, possibly related to the tumor, may circulate in blood (18,(20)(21)(22)(23)(24) or be deposited in tissues (25)(26)(27)(28) of patients with different types of malignancy, including leukemia (29 The present study was carried out, using the [125I]-Clq-binding test (30) and the Raji cell radioassay (23), to determine the incidence of circulating immune complexes in leukemia and to investigate their relationship to clinical and biological features of the disease and to prognosis. The serum Clq-binding material which was detected was further characterized by immunochemical and physical analysis.…”
Section: Introductionmentioning
confidence: 99%